Identification of a PATL2 missense variant (c.877G>T) disrupting canonical splicing and contributing to female infertility - Li, Hongyan; Lin, Yue; Ma, Weixu; Yu, Ting; Dong, Lingfeng; Chen, Yankun; Fan, Shuming; Luo, Guoqun; Zhang, Jingwen; Song, Ge (Frontiers in Genetics, 2025)
BackgroundPATL2 deficiency is a significant cause of female infertility. Although multiple PATL2 missense variants have been reported in prior studies, a number of these variants remain classified as variants of uncertain significance (VUS).MethodsWe present a patient of primary infertility characterized by oocyte maturation disorders and fertilization failure. Comprehensive genetic analysis was conducted through whole-exome sequencing (WES) to identify pathogenic variants, followed by Sanger sequencing for familial co-segregation analysis. Reverse transcription (RT-PCR), cDNA sequencing and quantitative RT-PCR were performed to validate the effect of the variant on pre-mRNA splicing.ResultsWe identified compound heterozygous variants in the PATL2 gene by WES: a pathogenic splice-site splicing variant (c.223-14_223-2del) and a missense variant (c.877G>T) initially classified as a VUS. Sanger sequencing confirmed that the proband carried biallelic variants, whereas her sisters with either wild-type genotypes or a single heterozygous variant exhibited normal fertility, supporting the co-segregation of the identified variants. Critically, RNA assays demonstrated that the missense variant c.877G>T disrupts canonical splicing of PATL2, resulting in exon 12 skipping.ConclusionThis study provides the first experimental evidence that a PATL2 missense variant (c.877G>T) can exert its pathogenicity through aberrant splicing, supporting its pathogenic reclassification and elucidating a genotype-phenotype correlation for PATL2 missense variants through functional assays.